Spherical nucleic acids for biomedical applications - Chunxin Xia; Hemei Cheng; Xinwei Hou; Yu Zhang; Xinchi Zhou; Qinglong Yan; Shuting Cao (Advanced Sensor and Energy Materials)
Spherical nucleic acids (SNAs) are a 3D spherical nanostructure composed of highly oriented, dense layers of oligonucleotides conjugated to a hollow or solid core. This structure allows SNAs to show resistance to nuclease degradation, enter into nearly all cells without transfection agents and enable precise interactions with target molecules. Based on superior biological properties, SNAs can be tailored for diverse biological applications, rendering them a flexible and biosafe tool for biological applications as well as an enabling platform for therapy. In this review, we mainly discuss the structure and conjugation mode of SNAs and focus on recent advances in their applications, such as biomedical detection, imaging, and drug delivery. Finally, the remaining challenges and future directions of SNAs are also discussed and proposed.